The roles and challenges of women entrepreneurship in the K-Economy / Firdaus Abdul Rahman...[et al.] - Abdul Rahman, Firdaus; Anuar, Azyyati; Daud, Mohd Shamsul (2010)
In the information age, knowledge is power. Knowledge, and its management, is becoming more well-known in today’s world because it can be distributed faster at cheaper cost with the information revolution and globalization that are related closely with the escalation of ICT. In earlier days, a competitive advantage in identifying the success of the economy of a country was dependent on the factors such as labour, land and natural resources. However, the ICT has changed the trends based on the potential on acquiring, generating, communicating and exploiting knowledge commercially, in order to be a global player and to be able to sustain long-term growth production. The Master Plan on K-economy will set the choices of strategies in key areas to transform Malaysia from an input-driven to a knowledge-driven economy which focuses on intellectual capital as a prime mover. Currently the omit development of the country is also contributed by the successful and committed women entrepreneurs that have increased dramatically. This paper will explore the roles and challenges faced by the women entrepreneurs in preparing themselves for the technology changes in the globalization of the knowledge-based economy. Further on, the paper will also discuss about the recommendations and suggestions to the women entrepreneurs in preparing and strengthening their ICT skills and knowledge.